The Role of Emotional Intelligence in the Maintenance of Depression Symptoms and Loneliness Among Children - Davis, Sarah K.; Nowland, Rebecca; Qualter, Pamela (Frontiers in Psychology, 2019)
In the current study we examined the impact of both trait emotional intelligence (TEI) and ability emotional intelligence (AEI) on the maintenance of loneliness and depressive symptoms over one year among children aged 9-11 years. Two hundred and thirteen children (54% male) completed the TEIQue-CF and the MSCEIT-YV at the first time point of the study, and the Child Depression Inventory and the Loneliness and Aloneness Scale for Children and Adolescents at Time 1 and, again, one year later. Findings indicate that emotional skills (AEI) are important for predicting the maintenance of depressive symptoms and loneliness in children over one year; emotional self-efficacies (TEI) are less influential, only contributing to long-term loneliness in girls. Moreover, whilst deficiencies in the ability to perceive and understand emotions were predictive of prolonged symptomatology, so, too, were proficiencies in using emotion to facilitate thinking and emotion management. Those findings carry important implications for EI theory and future research. They also indicate that EI interventions tailored to groups of ‘at risk’ school children may be useful for reducing specific profiles of internalizing symptoms. Programs targeting AEI skills may be universally helpful for reducing the likelihood that depressive symptoms and loneliness will be maintained over time in middle childhood; girls at risk for prolonged loneliness would additionally benefit from opportunities to bolster TEI.